Dystopian Dreams and Realities: Indian Young Adult Fiction and the Imaginations of Adolescent & Adolescence - Jain, Shubhangi (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This paper explores how Indian young adult (YA) dystopian fiction redefines adolescence. It studies four texts: Samit Basu’s Chosen Spirits (2020), Richa Mukherjee’s The Curse of Kuldhara (2021), Sharanya Manivannan’s Mermaids in the Moonlight (2021), and Kanishk Tharoor’s Stories About the Pandemic (2022). These novels present adolescence as resistance, vulnerability, and hybridity. Unlike many Western YA dystopias, which focus on isolation, Indian texts highlight community, intergenerational memory, caste and class struggles, and ecological survival. In Chosen Spirits, Delhi’s youth live under constant surveillance: “every move was being scored and streamed” (Basu, Chosen Spirits). Mukherjee’s The Curse of Kuldhara reminds readers that “the silence of an abandoned village refuses to forget” (Mukherjee, The Curse of Kuldhara). Manivannan’s mermaid narrator insists that “the sea holds stories of those who vanished beneath its waves” (Manivannan, Mermaids in the Moonlight). Tharoor’s stories capture the pandemic through haunting images, such as when “the city fell silent, as if even the walls were holding their breath” (Tharoor, Stories About the Pandemic). These works portray adolescents as fragile yet strong. They navigate myths, digital authoritarianism, caste divisions, and climate anxiety. Together, they show how dystopian fiction in India becomes a tool of pedagogy. It helps young readers understand surveillance, ecological crisis, and social inequality, while also offering hope through community and resilience.